Tecnologia lítica: análise do material lítico do sítio arqueológico Quizanga, Rosário do Catete, Sergipe - Almeida, José Edimarques Reis (2022)
This work intends to understand the stages of lytic production carried out by groups from the pre-colonial period that inhabited the locality of Sítio Quizanga, located in the hydrographic basin of the Japaratuba River, between Mocambo and Siriri Rivers, in the municipality of Rosário do Catete, Sergipe, Brazil. For that, we performed the analysis of the lithic material collected in the excavations of the referred Sítio from a technological point of view, by using the methodology of the operative chain, in order to understand the strategies undertaken and traditionally shared by cultural groups through the lithic artifacts’ “life history”, where all the stages of this process are observed, from the collection of raw materials, production, use and disposal or reuse.